2022
DOI: 10.3390/ijerph191711093
|View full text |Cite
|
Sign up to set email alerts
|

Post-Acute COVID-19 Sequelae in a Working Population at One Year Follow-Up: A Wide Range of Impacts from an Italian Sample

Abstract: Long COVID-19 is a term used to describe the symptomatic sequelae that develop after suffering from COVID-19. Very few studies have investigated the impact of COVID-19 sequelae on employment status. The aim of this research was to characterise sequelae of COVID-19 in a population of workers who tested positive for COVID-19, with a follow-up within one year of the acute illness, and to analyse the possible association between this and changes in the workers’ occupational status. In this retrospective cohort stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 39 publications
(40 reference statements)
1
19
0
Order By: Relevance
“…As a result, feelings of aimlessness, lack of perspective, insecurity, and uselessness became apparent. Similarly to our study, several participants from another sample also reported a change in their occupational status due to persistent health impairments after a COVID-19 infection ( 16 ). The umbrella review by Nittas et al ( 9 ) cites various studies in which a substantial proportion of respondents with long COVID were unable to work for at least 8 weeks.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…As a result, feelings of aimlessness, lack of perspective, insecurity, and uselessness became apparent. Similarly to our study, several participants from another sample also reported a change in their occupational status due to persistent health impairments after a COVID-19 infection ( 16 ). The umbrella review by Nittas et al ( 9 ) cites various studies in which a substantial proportion of respondents with long COVID were unable to work for at least 8 weeks.…”
Section: Discussionsupporting
confidence: 80%
“…Several interviewees from our sample stated that, as a result of the inability to work or other occupational limitations, the social environment became smaller or the number of face-to-face interactions decreased. Social consequences such as isolation or stigmatization due to a long absence from work are also reported by other studies which suggested to facilitate access to state vocational and retirement counseling and to provide support through social services or rehabilitation institutions (6,7,16).…”
Section: Key Findings Occupational Situation and Comparison With Furt...mentioning
confidence: 76%
See 1 more Smart Citation
“…COVID-19 has had an impact on occupational health both directly and indirectly. The direct impact was having to manage the contagion risk in the workplace and returning to work post COVID-19 ( 4 ), as well as the emerging problems related to long COVID-19 syndrome that are currently still being evaluated ( 5 ). The indirect effect of COVID-19 on the workplace has been on the organizational measures adopted to reduce its impact, remote working being the primary solution for many companies to reduce contagion risk; remote working has been itself an important source of psychological distress for workers worldwide ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Gibbs et al documented with a study on 112 desk workers that working from home was often associated with non-work sedentary resulting in declining physical functionality and worsened sleep quality [ 9 ]. Buonsenso et al showed that a significant percentage of previously infected subjects reported not feeling fully recovered at follow-up or a change in their job status highlighting the requirement for successful prevention campaigns and assessment of post-acute COVID-19 sequelae [ 10 ].…”
Section: Introductionmentioning
confidence: 99%